2016
DOI: 10.1016/j.bbadis.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Hexa (ethylene glycol) derivative of benzothiazole aniline promotes dendritic spine formation through the RasGRF1–Ras dependent pathway

Abstract: Our recent study demonstrated that an amyloid-β binding molecule, BTA-EG4, increases dendritic spine number via Ras-mediated signaling. To potentially optimize the potency of the BTA compounds, we synthesized and evaluated an amyloid-β binding analog of BTA-EG4 with increased solubility in aqueous solution, BTA-EG6. We initially examined the effects of BTA-EG6 on dendritic spine formation and found that BTA-EG6-treated primary hippocampal neurons had significantly increased dendritic spine number compared to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Several small GTPases have been characterized as enhancers of spine density, especially Cdc42 (Tashiro et al, 2000; Wegner et al, 2008; Kim et al, 2013; Jaudon et al, 2015) and Rac1 (Tashiro et al, 2000; Penzes et al, 2001; Penzes et al, 2003; Tolias et al, 2007; Bacon et al, 2013; Ueda et al, 2013; Dhar et al, 2014; Raynaud et al, 2014; Evans et al, 2015; Jaudon et al, 2015; Kim et al, 2015; Valdez et al, 2016); others have been shown to inhibit spine density, in particular Ras (Yang et al, 2013; Lee et al, 2016) and RhoA (Tashiro et al, 2000; Margolis et al, 2010; Alder et al, 2013; Kim et al, 2015). Furthermore, modulators of activity for Ras (Pham and Rotin, 2001), Cdc42 (Hayakawa et al, 2008; Yamaguchi et al, 2008), and RhoA (Margolis et al, 2010; Lin et al, 2011; Papadimitriou et al, 2012) have been shown to be degraded by the proteasome, as well as Rac1 (Torrino et al, 2011; Zhao et al, 2013) and RhoA themselves (Wang et al, 2003; Cheng et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several small GTPases have been characterized as enhancers of spine density, especially Cdc42 (Tashiro et al, 2000; Wegner et al, 2008; Kim et al, 2013; Jaudon et al, 2015) and Rac1 (Tashiro et al, 2000; Penzes et al, 2001; Penzes et al, 2003; Tolias et al, 2007; Bacon et al, 2013; Ueda et al, 2013; Dhar et al, 2014; Raynaud et al, 2014; Evans et al, 2015; Jaudon et al, 2015; Kim et al, 2015; Valdez et al, 2016); others have been shown to inhibit spine density, in particular Ras (Yang et al, 2013; Lee et al, 2016) and RhoA (Tashiro et al, 2000; Margolis et al, 2010; Alder et al, 2013; Kim et al, 2015). Furthermore, modulators of activity for Ras (Pham and Rotin, 2001), Cdc42 (Hayakawa et al, 2008; Yamaguchi et al, 2008), and RhoA (Margolis et al, 2010; Lin et al, 2011; Papadimitriou et al, 2012) have been shown to be degraded by the proteasome, as well as Rac1 (Torrino et al, 2011; Zhao et al, 2013) and RhoA themselves (Wang et al, 2003; Cheng et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The signaling pathways linking enhanced neural activity to new spine growth are currently being elucidated; many converge upon Rho GTPases as critical regulators of spinogenesis (Tolias et al, 2011; Penzes and Cahill, 2012; Saneyoshi and Hayashi, 2012; Lai and Ip, 2013; Um et al, 2014; Kim et al, 2015; Nishiyama and Yasuda, 2015; Lee et al, 2016). In addition, we recently identified the proteasome as a key regulator of activity-dependent spine outgrowth (Hamilton et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has reported that BTA-EG 4 and BTA-EG 6 could promote spine density increases in vitro in murine primary hippocampal neurons (37) and BTA-EG 4 could promote spine density increases in vivo in the hippocampus of wt mice and a 3ϫ tg mouse model for AD (18,19). The increase in spine density in neurons by BTA-EG 4,6 correlated with an increase in expression of RasGRF1 compared with control cells (37). In order to test whether the spinogenic activity induced by compounds 1-3 operated along a similar mechanistic path as BTA-EG 4,6 , we analyzed the effects of these compounds on the expression level of both RasGRF1 and active Ras in rat-dissoci- M BAM1-EG 6 on spine density.…”
Section: Design and Evaluation Of Benzothiazole Amphiphiles (Bams) 1-mentioning
confidence: 97%
“…Effects of BAMs 1-3 on Dendritic Spine Density-BTA-EG 6 was first used to assess increases in spine density in primary hippocampal neurons as a control due to its previously published ability to increase spine density (37). To visualize all spines, we used a virally transfected membrane-targeting pal-GFP that is known to reliably fluorescently label dendritic spines (38 -40).…”
Section: Design and Evaluation Of Benzothiazole Amphiphiles (Bams) 1-mentioning
confidence: 99%
“…To date, relatively few compounds have been shown to increase dendritic spine density [14][15][16][17][18][19][20][21][22]. For instance, we have previously reported that benzothiazole amphiphiles (BAMs) can increase dendritic spine density in primary rat hippocampal neuronal culture [15] as well as in vivo in wild-type mice and in a 3xTg mouse model for AD [23][24][25]. These initial reports showed that BAMs are able to improve memory and learning in rodents by a RasGRF1 (a guanine nucleotide release factor involved in regulation of dendritic spine formation)-associated mechanism for promoting dendritic spine formation.…”
mentioning
confidence: 99%